The Influence of Packaging Methods towards Chemical Quality of Ground Beef Jerky - Sugiarto, Sugiarto (AgriSains, 2019)
Preservation and processing of meat into beef jerky can extend storage life, but it is still determined by the packaging method. The purpose of this study was to determine the effect of packaging method on the level of change in the chemical quality of ground beef jerky. This research was conducted at the Laboratory of Animal Product Technology, Faculty of Animal Husbandry and Fishery, as well as the Agroindustry Laboratory of the Faculty of Agriculture, Tadulako University from 4 October 2018 to 12 January 2019. The research designed by applying a Completely Randomized Design (CRD) with 5 treatments and 3 replications, with treatments D0 = jerky without packaging, D1= jerky completely packed up, D2= jerky + Aluminum foil zipper with air cavity ± 0.0019 within 1 cm, D3= D0 + Aluminum foil zipper with air cavity ± 0.0038 within 1 cm, D4= D0 + Aluminum foil zipper with air cavity ± 0.0057 within 1 cm. The observed parameters were content of protein, fat and water. The results showed that ground beef jerky with different packaging treatments, had no significant effect (P> 0.01) on protein content (D0= 37.20; D1= 38.17; D2= 38.37; D3= 38.21; D4= 28.37%) and the fat content of ground beef jerky (D0= 6.52 ±; D1= 6.65; D2= 6.67; D3= 6.67; D4= 6.77%), but have significant effect (P <0.05) of jerky water content (D0= 22.08; D1= 25.28; D2= 24.60; D3= 23.50; D4= 22.12). The Duncan's test of the water content significantly affected, after storage for 3 months. Water content is an important component in jerky, because it also determines freshness and durability. It also affects the appearance, texture and taste of food. Therefore, the method of packaging using aluminum foil zipper with an air cavity of ± 0.0038 1 cm produces the best chemical quality of ground beef jerky.Keywords: Ground beef jerky, packaging method, storage life